Synthetic observations of star formation and the interstellar medium - Haworth, Thomas; Glover, Simon; Koepferl, Christine Maria; Bisbas, Thomas G.; Dale, James (New astronomy reviews, 2018)
Synthetic observations are playing an increasingly important role across astrophysics, both for interpreting real observations and also for making meaningful predictions from models. In this review, we provide an overview of methods and tools used for generating, manipulating and analysing synthetic observations and their application to problems involving star formation and the interstellar medium. We also discuss some possible directions for future research using synthetic observations.
Gesehen am 22.10.2019